Efektivitas Latihan Pull Down dan Alternate Squat Terhadap Peningkatan Kecepatan Renang Gaya Dada - Bagaskara, Zidane Artya; Hidayah, Nida'ul; Rismayadi, Alen (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
It is known that both leg strength and arm strength have a significant influence on breaststroke swimming speed. Therefore, the purpose of this research is to determine whether there is a significant impact of Pull Down and Alternate Squat exercises together on the 25-meter breaststroke swimming speed. This research method employs a Quasi-Experiment (pseudo-experiment). The sample consists of 10 members of the Bandung City Shining Star SC who can consistently and continuously participate in the training program and already have a foundation in breaststroke swimming. The instrument used is a 25-meter breaststroke swimming test in a 25-meter pool without a poolside start. The research design used in this study is the One Pretest-Posttest Group Design. Data is processed using the t-test to determine whether there is a difference in variables between the pretest and posttest in the experimental group. The results of the research indicate a significant impact of Pull Down and Alternate Squat exercises together on the 25-meter breaststroke swimming speed.